STRATEGI PENGEMBANGAN BISNIS "DRUCKENPHOTOBOOTH" DENGAN MENGGUNAKAN LEANCANVAS - Muhammad Alrachdan Renatin (2020)
Drucken Photobooth is a service provider of photobooth services. With Drucken photobooth, the person who attend an event will document their moments of togetherness with a photo in this photobooth and immediately received the print result. However, Drucken Photobooth is not a new business in its market, but rather as an newcomer of the photobooth market. The aim of the study was to design the Drucken Photobooth Business development strategy using the Lean Canvas method. Other supporting methods are SWOT, IFAS-EFAS, TOWS, and VRIO Framework. From the analysis, there is some main focus of the strengths of Drucken Photobooth. The mains focus are HR and equipment completeness. Both of these advantages must still be developed because they are included in the advantages that are easy to replicate and are not sustainable. The recommended strategy is to develop marketing strategies, expand photography services, and also increase the strengths that Drucken Photobooth already had.